Characteristics and Clinical Outcomes of Patients on Mechanical Ventilation in the Coronary Care Unit of a Tertiary Care Hospital in Bangladesh - Shafi, Masuma Jannat; Nasrin, Sahela; Iqbal, Md Jabed (Bangladesh Heart Journal, 2023)
Background: This study was undertaken to evaluate clinical characteristics, indications, outcomes, and factors affecting outcomes in adult patients on mechanical ventilation admitted to CCU that will help planning of proper MV management programs. There are few studies in the coronary care unit (CCU) population and even fewer from developing countries. Methods: All adult patients received MV at Ibrahim cardiac hospital CCU between June 2019 and July 2020 were prospectively recruited. Different demographic, indications, type and characteristics of ventilation, concomitant complications and treatment, outcomes, clinical and laboratory variables were recorded at the initiation of mechanical ventilation and daily, all throughout the course of MV & thereafter. Results: Out of 1563 patients admitted to the CCU, 138 patients received IMV. Mean age was 64.2±12.1. Male were predominant (71.7% vs. 28.3%). DM was the most common (81.9%) risk factor. Reasons for intubation were as follows: type 1 respiratory failure (40%), type II respiratory failure (35%), and post cardiac arrest (25%). Mostly used mode of ventilation was A/C VCV (96.4%). Invasive MV was associated with high APACHE II score, low admission PH, Po2, and high Pco2. A higher in-coronary care unit death was observed in MV patients (65.2%) while that for MI (70.3%) than survivors (34.8%). CAG±PCI was (5.8%) keeping on MV or after extubation. The mean duration of MV, stay in CCU and hospital were (53.5±5.8, 80.5±7.6 and 128.8±12.0) hours respectively. The main factors independently associated with increased mortality were (i) pre-MV factors: age, APACHE II scores, acute left ventricular failure, and cardiogenic shock, sepsis (64.2±12.1, 39.1±19.2, 65.9%, 81.2%, and 70%). (ii) Patient management factors during ventilation: without positive end-expiratory pressure (65.6%) (iii) Factors occurring over the course of MV: PaO2/FiO2<100 (61.2±18.75) and development of renal failure (47.8%), VAP (40.6%), MODS (21.0%) & ARDS (8.7%) after initiation of MV. Conclusion: Outcome among mechanically ventilated patients depended on the factors (including patient’s demographics, nature of associated morbidity, characteristics of MV received, and conditions developing over the course of MV). These factors may be present before or develop after initiation of MV as well as on the development of complications and the management protocols in the CCU. Bangladesh Heart Journal 2023; 38(1): 22-31